(untitled) (Web of Teachers: Inderscience Research, 2026)
Economic instability is a persistent and formidable challenge that impacts individuals at all levels of society. In recent years, fluctuations in global and national economies have created periods of uncertainty, directly affecting the financial and psychological well-being of various demographics. Among the most affected groups are university students, who are at a critical juncture in their lives as they transition from educational environments to professional careers. Students often find themselves navigating the demands of academic life while simultaneously grappling with concerns about their financial futures. In the context of economic instability, students’ approaches to saving and their resultant levels of anxiety display complex and multilayered characteristics.